Development of Web-Based IoT Smart Fire and Gas Leak Detection System - Mohd Hairudin, Nureen Haziqah; Nayef Abdulwahab Muhammed Alduais, (Applied Information Technology And Computer Science, 2025)
This project successfully created an IoT-based Smart Fire and Gas Leak Detection System for use in restaurant environments, overcoming common difficulties such as delayed detection of fires or gas leaks, ambiguous alarm signals, and the possibility of incidents being missed during off-shift hours. The system was created with three major purposes in mind: to create a dependable and efficient sensor setup, to use IoT technology with sensors, alarms, and WhatsApp messages for real-time alerts, and to confirm that the system operated properly through extensive testing. The hardware used in the development was the Wemos D1 ESP8266, MQ-2 Gas Sensor, IR Flame Sensor and DHT11 Temperature Sensor. The Arduino IDE was used for programming, ThingSpeak for cloud data monitoring, and PHP, Laravel and MySQL to create the web-based monitoring system. A rigorous test strategy and User Acceptance Testing (UAT) were carried out to ensure that the system was functional, reliable and simple to use. Testing results showed that the device successfully decreased the risk of fires and gas leaks in restaurants. Overall, the project proved how IoT technology can be used to improve workplace safety, speed up emergency responses and assist prevent major events.